Hebraica veritas versus Septuaginta auctoritatem does a canonical text of the Old Testament exist? - Carbajosa, Ignacio 1967-; Stevenson, Paul S.; Schenker, Adrian 1939- (Eugene, Oregon Pickwick Publications, 2024)
"At the end of the fourth century, Jerome decided to translate the Old Testament into Latin from the Hebrew manuscripts that were available to him, and not from the "traditional" Greek text. This fact provoked a reaction from Augustine, who considered that the Greek translation of the LXX must be the starting point of every translation, since it had the authority of the apostles. The two great figures of the Latin West engaged in a dialectical battle in which we find clearly delineated the two principles which are in tension and which have determined the reception of the biblical text down to our time: the value of the "original" text (hebraica veritas) and the authority of the text received by the church (Septuaginta auctoritas). In facing this "battle," we are dealing with some very up-to-date questions: Is it possible to speak of a canonical text of the Old Testament? In what language is that text? On what text should our liturgical translations be based? Is there an "original" text of the Bible? Can an ancient version be superior to the text it is translating? What is the value of the LXX?" --
Introduction: On the 16th centenary of the death of Saint Jerome -- The polemic between Jerome and Augustine: Should the Old Testament be translated from the Hebrew or from the Greek? -- The textual differences between the Hebrew and the Greek Bibles -- The Hebraica Veritas: Lights -- The Hebraica Veritas: Shadows -- The Septuaginta Auctoritas: Lights -- The Septuaginta Auctoritas: Shadows -- A word from the church: The decree of Trent -- The Latin Vulgate: A work of synthesis -- Lessons from the past for overcoming the polemic -- The synthetic principle in the liturgical translations.
Includes bibliographical references (pages 115-122) and indexes
Translated from the Spanish
Keywords: Bible -- Versions; Bible; Bible -- Canon